2013
DOI: 10.1002/pola.26822
|View full text |Cite
|
Sign up to set email alerts
|

Design and property of thermoresponsive core-shell fluorescent nanoparticles via RAFT polymerization and suzuki coupling reaction

Abstract: The polymerization of a 2,7-dibromocarbazole-containing functional monomer, 6-(2,7-dibromo-9H-carbazol-9yl)hexyl methacrylate (DBCzMA), was successfully carried out via the reversible addition-fragmentation chain transfer (RAFT) technology. The polymerization behavior possessed the feature of "living"/controlled radical polymerization, for example, the first-order kinetics, the linear increase of the molecular weight of the polymer with the monomer conversion and relatively narrow molecular weight distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Soft materials are particularly interesting candidates for in situ imaging due to the fact that in solution their morphology can be manipulated by a broad range of stimuli including metals, pH, temperature, light, redox chemistry, ultrasound, DNA hybridization, and enzymes . Furthermore, organic liposomes and synthetic polymer vesicles have been imaged via in situ TEM but only as stationary, static objects, ,, which have sometimes appeared crenated as if dehydrated .…”
mentioning
confidence: 99%
“…Soft materials are particularly interesting candidates for in situ imaging due to the fact that in solution their morphology can be manipulated by a broad range of stimuli including metals, pH, temperature, light, redox chemistry, ultrasound, DNA hybridization, and enzymes . Furthermore, organic liposomes and synthetic polymer vesicles have been imaged via in situ TEM but only as stationary, static objects, ,, which have sometimes appeared crenated as if dehydrated .…”
mentioning
confidence: 99%
“…To date, PPM of RDRP derived polymers using Pd-SMC is underutilized, in spite of the minimal limitations impeding its implementation outside the interference of thiol or thioester blocking groups. , Accounts of Pd-catalyzed cross-coupling for PPM have been reported; however, focus has resided primarily on Sonogashira cross-coupling of functional alkynes onto bromine functional homopolymers , and iodine functional hyperbranched polymers . In the limited instances of Pd-SMC and RAFT, Pd-SMC has been almost exclusively explored as a tool for creating core–shell nanoparticles, as a cross-linking method for homopolymers and block copolymers, and for synthesizing cyclic bottlebrushes via a “grafting-to” approach . Mori and co-workers demonstrated RAFT polymerization of bromophenyl vinyl sulfide and its subsequent Pd-SMC; however, a limited scope of boronic acids were explored consisting of two fully hydrocarbon boronic acids .…”
Section: Introductionmentioning
confidence: 99%
“…Mori et al [34] reported the first successful synthesis of a carbazole-based side chain polymer (poly(N-vinylcarbazole)) using the RAFT technique. Most recently, Zhu et al [35] prepared an amphiphilic copolymer poly(DBCzMA-b-NIPAM) through a two-step RAFT reaction using poly(6-(2,7-dibromo-9H-carbazole-9-yl) hexyl methacrylate) (poly(DBCzMA)) as the macro-chain transfer agent (macro-CTA) and poly(N-isopropylacrylamide) (PNIPAM) as the second monomer. Consequently, the modification of 2,7-dibromide groups in poly(DBCzMA-b-NIPAM) using the Suzuki coupling method (which reacted with a 4,4,5,5-tetramethyl-1,3,2-dioxaborolan-based carbazole monomer) obtained a poly(2,7-carbazole)-containing crosslinked polymer with the appearance of uniform core-shell fluorescent nanoparticles dissolved in water.…”
Section: Introductionmentioning
confidence: 99%